Determination of selenium concentration and glutathione concentrations in preeclampsia women in Balad city- Salah al-deen governorate - Shaker M. M Al-Jobori; Waser, S, Khlaf; Yaseen Khashman. Hussein; Mossa M. Marbut (Journal of Madenat Alelem University College, 2019)
Background: Selenium concentration was measured in women under oxidative stress and was found lower than normal healthy women. Also, there was significant reduction in serum Se in type 2 diabetic patients. Whole blood and plasma selenium and red cell glutathione concentrations were significantly lower in the patients with chronic liver disease as compared with the normal healthy controls. The aim of the study is Determination of selenium concentration and glutathione concentrations in preeclampsia women in Balad city- Salah al-deen governorate. Subjects and methods: A cross sectional study was done in Balad hospital – Salah al-deen governorate. A 90 pregnant women were participated in the present study, (60 women with pregnancy induced hypertension and 30 normotensive pregnant women). In the present study, there is significant elevation in the concentration of MDA in the serum of hypertensive pregnant women as compare with normotensive pregnant women, (p≤0.01). However, there is significant reduction in the concentration of glutathione (GSH) in the serum of hypertensive pregnant women as compare with normotensive pregnant women, (p≤0.01). Also, there is significant reduction in the concentration of serum selenium in the serum of hypertensive pregnant women, as compare with normotensive pregnant women, (p≤0.01). The present study concludes that there was a highly significant trend for decreasing plasma selenium concentrations in hypertensive pregnant women as compare to normal pregnant and pre-eclamptic women.